ANALISIS YURIDIS PENGUASAAN TANAH SEMPADAN PANTAI OLEH MASYARAKAT DI ATAS TANAH PERHUTANI (Studi Penguasaan Tanah Sempadan Pantai Bayuran Desa Tubanan Kabupaten Jepara) - Amelia, Natasya (Law Research Review Quarterly, 2024)
Land control refers to the rights or control of an individual or group over an area or land. Land control can involve various aspects, including ownership, use, and control over the resources on or within the land. Land control in coastal areas raises complex issues. This study aims to analyze coastal land control, focusing on the case study of Bayuran Beach, Tubanan Village, Jepara Regency. The research method used in this study is empirical juridical with a qualitative research approach and data collection techniques through interviews and documentation studies. The research focuses on Evidence of Land Control and Local Government Actions Regarding Coastal Land Control in Jepara Regency. The results of the study show that (1) The coastal land of Bayuran Beach is owned by Perhutani and can be proven with a valid certificate from the National Land Agency (BPN) and other supporting documents. (2) Residents only make payments for Land and Building Tax, but the Tax Notification Letter is not recognized as proof of land ownership. (3) More assertive actions are needed by the Local Government, especially Perhutani, because the establishment of illegal permanent buildings still occurs. Other efforts are needed by conducting socialization to the community, improving regulations, and enforcing more effective laws to address these issues.